2021
DOI: 10.1111/jocs.15479
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐implant right ventricular free wall strain predicts post‐LVAD right heart failure

Abstract: Background The aim of this study is to evaluate the predictive utility of preoperative right ventricular (RV) global longitudinal strain (GLS) and free wall strain (FWS) on outcomes following left ventricular assist devices (LVADs) implantation. Methods Preoperative transthoracic echocardiograms were retrospectively reviewed in adults undergoing continuous‐flow LVAD implantation between 2004 and 2018 at a single center. Patients undergoing pump exchange were excluded. RV GLS and FWS were calculated using comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Предложено использовать многочисленные параметры дооперационного лабораторного, гемодинамического, эхокардиографического и МРТобследования для прогнозирования развития ПЖД как в ранние, так и отдаленные сроки после имплантации ЛЖО (табл. 2) [7,[14][15][16]. Продемонстрирована высокая прогностическая значимость не доп ле ровского изображения миокарда (спекл-трекинг эхокардиографии, магнитно-резонансная томография) с определением сегментарной и глобальной деформации ПЖ для прогнозирования развития его дисфункции при различных клинических ситуациях, включая имплантацию ЛЖО [17].…”
Section: Discussionunclassified
“…Предложено использовать многочисленные параметры дооперационного лабораторного, гемодинамического, эхокардиографического и МРТобследования для прогнозирования развития ПЖД как в ранние, так и отдаленные сроки после имплантации ЛЖО (табл. 2) [7,[14][15][16]. Продемонстрирована высокая прогностическая значимость не доп ле ровского изображения миокарда (спекл-трекинг эхокардиографии, магнитно-резонансная томография) с определением сегментарной и глобальной деформации ПЖ для прогнозирования развития его дисфункции при различных клинических ситуациях, включая имплантацию ЛЖО [17].…”
Section: Discussionunclassified
“…The current findings of RV longitudinal strain in RV failure following LV assist device implantation are shown in Table 7 . Dufendach et al [ 15 ] demonstrated that reduced 2D-RVFWLS before LVAD implantation was associated with higher incidence of RV failure after the implantation of a LVAD. Therefore, 2D-RVFWLS was a powerful predictor of RV failure following LVAD implantation.…”
Section: Rv Failure Following LV Assist Device Implantationmentioning
confidence: 99%
“…In addition, RV dysfunction has been recognized as a powerful independent predictor of poor prognosis [ 11 , 12 ]. Therefore, accurate evaluation of RV function is helpful for risk stratification in patients with HF, so as to guide clinicians to choose the best treatment and improve the prognosis of patients [ 13 , 14 , 15 , 16 , 17 , 18 ]. Currently, cardiac magnetic resonance (CMR) imaging remains the gold standard for RV volumes and function assessment.…”
Section: Introductionmentioning
confidence: 99%
“…However, utility of this measure in predicting RHF is unclear, and reproducibility and availability of the software package are known challenges [ 22 , 40 ]. RV free wall strain has been predictive of RHF following LVAD implantation [ 38 , 41 , 45 , 46 ] and is a promising marker for clinical use.…”
Section: Diagnosis and Recognition Of Right Heart Failurementioning
confidence: 99%